Löpönvaara: A new phosphorus‐rich iron meteorite from Finland - Kotomaa, Laura; Väisänen, Markku; Heinonen, Jussi S.; Mäkilä, Ermei; O'Brien, Hugh; Peltola, Arto (Wiley, 2026)
Löpönvaara is a rare new phosphorus-rich iron meteorite find from Löpönvaara, Finland. The ~164 g meteorite was discovered in 2017 from the same area as the ungrouped Lieksa pallasite. Löpönvaara was classified as an ungrouped iron meteorite due to its unusually high concentration of P (>4 wt%), coupled with a moderate concentration of Ni (~11 wt%), and Ga–Ge abundances in the “III” range. The meteorite consists of ~75 vol% kamacite and ~22 vol% schreibersite, with accessory troilite (<0.1 vol%), and minor terrestrial weathering products. The kamacite in Löpönvaara occurs as three different types: (1) rare, large 2–5 mm partially resorbed clasts; (2) round, ≤0.5 mm partially resorbed clasts; and (3) small, several tens of μm to sub-μm exsolution blebs and globules in the matrix. Schreibersite occurs solely as microscopic matrix material in between the type (1) and (2) kamacite clasts. The lack of taenite and the overall compositional and textural features of Löpönvaara suggest that it retained its composition possibly from a P-rich portion of immiscible melt at late stages of fractional crystallization, but its textural features suggest that the meteorite suffered impact-related metamorphism. The meteorite has no close textural or compositional affinities, which makes it unique and an important target for future studies.